The 2007 Meltdown in Structured Securitization - Caprio, Gerard, Jr.; Demirgüç-Kunt, Asli; Kane, Edward J. (World Bank, 2012)
The intensity of the crisis in financial markets has surprised nearly everyone. The authors search out the root causes of the crisis, distinguishing them from scapegoating explanations that have been used in policy circles to divert attention from the underlying breakdown of incentives. Incentive conflicts explain how securitization went wrong, why credit ratings proved so inaccurate, and why it is superficial to blame the crisis on mark-to-market accounting, an unexpected loss of liquidity, trends in globalization, and deregulation in financial markets. The authors' analysis finds disturbing implications of the crisis for Basel II and its implementation. They conclude by drawing out lessons for developing countries and identifying reforms that would improve incentives by increasing transparency and accountability in government and industry alike.